Pre-treatment of laundry greywater by steel slag for safe disposal - Ramdzan, S. N.; Mohamed, R. M. S. R.; Kamaruzaman, N. H.; A. Gheeti, A. A. S.; Hamdan, R.; Musa, Sabariah (2022)
Direct discharge of laundry greywater without any water pre-treatment in the drainage system has become a common practice in Malaysia. The study aimed to utilise steel slag as an adsorbent material for commercial laundry shop runoff (CLSR) to reduce chemical oxygen demand (COD) and total phosphorus (TP). Optimisation of the pollutants removal efficiency in CSLR by steel slag used Response Surface Methodology (RSM) using independent variables; different percentages of CLSR with tap water and contact time. The highest removal efficiency obtained for COD was 54.49% at 100% CLSR with tap water and 60 minutes of contact time. TP removal efficiency was 45.45% at 10% CLSR with tap water and 90 minutes of contact time. Thus, steel slag can increase the pH value, reducing the COD and TP values from CLSR in a short period. Hence, steel slag has the potential to be included in the “pre-treatment” system for CLSR based on its performance at COD and TP removal efficiency. From RSM, the model Fvalue and P-value for COD and TP were 5.89 and 10.62, 0.0166 and 0.0036, respectively. These values validated that the model was significant. Therefore, the study can contribute to the safe disposal of untreated laundry greywater to minimise environmental degradation.